Večkriterialno optimiranje avtomobilske konstrukcije z uporabo metode končnih elementov - Glavač, Matej (Strojniški vestnik, 2007)
Motor-vehicle development tends to be supported by the use of computer-aided numerical methods in the early development phase. Prior to manufacturing the first prototype it is required to ensure the requested vehicle-life expectancy, the vehicle's behaviour in a collision, passenger comfort while driving, etc. The listed target values depend on many other influential parameters. The stresses occurring on the analyzed part are only one of the target values that need to be considered in the development stage. Automated processes for the optimization of the vehicle construction are often applied due to the complexity of modern numerical models. Today, the use of parametric FEM models makes it possible to identify and optimize the main parameters, such as the wall thickness of the construction and the topological changes of the surface. This paper explains the procedure for a multicriterial optimization of a car's structure, based on a systematic combination of commercial and non-commercial computer programs performing engineering analyses of car constructions with the FEM. The computer programs are upgraded with specially designed interfaces that enable automated communication. The optimization itself is based on genetic and gradient algorithms. The openness of the system enables the identification and optimization of parameters, which influence the target values and stem from different static FEM analyses, dynamic FEM analyses, collision analyses, etc. The reduction procedure for more independent target values to a single target value that is later optimized is also explained. The example illustrates the applicability of the developed procedure.
Keywords: automotive industry; avtomobilska industrija; optimiranje; metoda končnih elementov; finite element method; topologija; genetski algoritmi